Comparison of Tenses in English and Uzbek Grammar - kizi, G’ofurova Mo’tabarxon Lutfillo; Ravshanjonovna, Karimjonova Shahlo (Journal of Innovation in Education and Social Research, 2025)
This article explores the similarities and differences between the tense systems of English and Uzbek languages. While English has a well-developed system of grammatical tenses, Uzbek relies more heavily on aspect and context. This comparative study highlights the key distinctions and provides examples to aid language learners and linguists.